889 An Audit of Indications for Emergency Abdominal X-Rays. (19th August 2022) - Masoodi, S; Van, PTM; Farzaneh, SB; Cribb, E; Pawa, N
Abstract: Background: Historically, abdominal X-rays (AXRs) have played an essential role in diagnosis of the acute abdomen. With the advent of other imaging modalities and the increasing need for efficiency in time, the utility of AXRs has been clarified by the RCR iRefer guidelines. Aim: To assess the congruence between indications of AXR requests and the recommendations provided by the RCR iRefer guidelines. Method: All AXRs performed over a 6-week period in the trust were identified retrospectively from our electronic database. Initial indications were subsequently compared with the current guidance and consultant radiologist reports. Results: Out of 575 AXRs performed, 36 (6%) had no indication documented on the request. Of the remaining 539, 364 (68%) of AXRs performed met the RCR iRefer guidance. Furthermore, 496 (86%) of AXRs performed were reported as normal. 35% of AXRs that met the guidance underwent further imaging, of which 60% showed abnormality. Of those that did not meet the current criteria, abdominal pain and toxic megacolon were the most frequently documented indications. Conclusions: One third of AXRs did not meet the RCR iRefer guidelines and were therefore requested inappropriately. Despite the remaining two thirds of requests being appropriate, over one third required further imaging in the form of CT/US. Moreover, less than one fifth of the total scans were interpreted as abnormal. This questions whether the current guidance requires revision and whether this imaging modality is over utilised with little effect on clinical outcomes.